Battery cell, battery, electric device
Patent Information
- Application Number
- CN202510435625.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2026-10-16
AI Technical Summary
[0014] In this embodiment, the negative electrode film is a double-layer design. The graphite material in the first negative electrode active layer accounts for a smaller mass percentage than that in the second negative electrode active layer. The interlayer spacing and specific surface area of the active material coating on the negative electrode sheet are larger, providing more transport channels for lithium ions, thereby reducing the risk of lithium plating. It also helps to reduce the damage to the electrode structure caused by the volume expansion of the active material and improve the cycle stability of the battery. At the same time, it reduces the internal resistance of the battery cell and improves the rate performance and charge/discharge efficiency.
Smart Images

Figure CN122930836A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more specifically, to a battery cell, a battery, and an electrical device. Background Technology
[0002] With increasing environmental pollution, the new energy industry is attracting more and more attention. Within the new energy industry, battery technology is a crucial factor in its development.
[0003] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, capacity, and reliability. Therefore, improving the cycle performance and rate performance of individual battery cells is a pressing issue that needs to be addressed. Summary of the Invention
[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a battery cell to improve the cycle performance and rate performance of the battery cell.
[0005] To achieve the above objectives, this application provides a battery cell, a battery, and an electrical device.
[0006] In a first aspect, a battery cell is provided, comprising: a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer, the negative electrode film layer being disposed on at least one surface of the negative current collector, the negative electrode film layer comprising graphite material; the interlayer spacing of the graphite material being 0.3354 nm to 0.3370 nm; the actual specific surface area BET1 of the graphite material and the theoretical specific surface area BET2 of the graphite material satisfying: 10 ≤ BET1 / BET2 ≤ 30; where BET2 = 6 / (ρ × Dv50), ρ being the compacted density of the graphite material, in g / cm³. 3 Dv50 represents the volumetric particle size distribution of graphite materials, in μm.
[0007] In the embodiments of this application, when the interlayer spacing of the graphite material is within the above-mentioned range, it has a larger interlayer spacing, which is beneficial for the movement of lithium ions between layers, reduces the interlayer expansion amplitude after lithium intercalation of graphite, reduces the rebound rate of the electrode, and improves the cycle performance of the battery cell. At the same time, when the actual specific surface area of the graphite material is within the above-mentioned range as well as the theoretical specific surface area, it indicates that the graphite material has a higher actual specific surface area, increases the reactive sites, and helps to improve the rate performance.
[0008] In one possible implementation, the interlayer spacing of the graphite material is 0.3359 nm to 0.3361 nm.
[0009] In one possible implementation, the actual specific surface area BET1 of the graphite material and the theoretical specific surface area BET2 of the graphite material satisfy: 12≤BET1 / BET2≤24.
[0010] In the embodiments of this application, when the ratio of the actual specific surface area BET1 to the theoretical specific surface area BET2 of the graphite material is greater than or equal to 12, the graphite material has a larger specific surface area, providing more active sites, promoting the insertion and extraction of lithium ions, improving the charging capacity of the battery, and enhancing the rate performance; when the ratio of the actual specific surface area BET1 to the theoretical specific surface area BET2 of the graphite material is less than or equal to 24, it is beneficial to reduce the occurrence of side reactions and improve the cycle performance of the battery cell.
[0011] In one possible implementation, the true specific surface area BET1 of the graphite material satisfies: 2m² 2 / g≤BET1≤6m 2 / g. Optionally, 2.2m 2 / g≤BET1≤4.5m 2 / g.
[0012] In the embodiments of this application, when the specific surface area of the graphite material is within the above-mentioned range, it provides more active sites, which can improve the charging capacity and rate performance of the battery, while reducing the side reactions between the negative electrode active material and the electrolyte, forming a larger area of solid electrolyte interphase (SEI) film, and taking into account the cycle performance of the battery cell.
[0013] In one possible implementation, the negative electrode film layer includes a first negative electrode active layer and a second negative electrode active layer, with the first negative electrode active layer disposed between the negative electrode current collector and the second negative electrode active layer; the mass ratio A of graphite material in the first negative electrode active layer and the mass ratio B of graphite material in the second negative electrode active layer satisfy: A < B.
[0014] In this embodiment, the negative electrode film is a double-layer design. The graphite material in the first negative electrode active layer accounts for a smaller mass percentage than that in the second negative electrode active layer. The interlayer spacing and specific surface area of the active material coating on the negative electrode sheet are larger, providing more transport channels for lithium ions, thereby reducing the risk of lithium plating. It also helps to reduce the damage to the electrode structure caused by the volume expansion of the active material and improve the cycle stability of the battery. At the same time, it reduces the internal resistance of the battery cell and improves the rate performance and charge / discharge efficiency.
[0015] In one possible implementation, 1.02 ≤ B / A ≤ 1.10.
[0016] In the embodiments of this application, when the ratio of the mass percentage of graphite material in the first negative electrode active layer to the mass percentage of graphite material in the second negative electrode active layer is greater than or equal to 1.02, it is beneficial to reduce the risk of lithium plating, improve the reliability of the battery cell, and at the same time reduce the internal resistance of the battery cell and improve the rate performance; when the ratio is less than or equal to 1.10, it avoids the reduction of lithium ion transport efficiency due to excessive surface active material, and takes into account the cycle performance of the battery cell.
[0017] In one possible implementation, the negative electrode film layer includes a binder; the mass percentage M of the binder in the first negative electrode active layer and the mass percentage N of the binder in the second negative electrode active layer satisfy: N < M.
[0018] In the embodiments of this application, the amount of binder added in the first negative electrode active layer is greater than the amount of binder added in the second negative electrode active layer. This can improve the adhesion of the negative electrode sheet and reduce the loosening and powdering problems of the negative electrode active material while keeping the total amount of binder unchanged, thereby improving the reliability of the battery cell.
[0019] In one possible implementation, 0.5 ≤ N / M ≤ 0.8.
[0020] In the embodiments of this application, when the ratio of the amount of binder added in the first negative electrode active layer to the amount of binder added in the second negative electrode active layer is within the above range, the adhesion of the electrode sheet can be improved while taking into account the rate performance of the battery.
[0021] In one possible implementation, the volumetric particle size distribution Dv50 of the graphite material satisfies: 16 μm ≤ Dv50 ≤ 20 μm. Optionally, 16.5 μm ≤ Dv50 ≤ 17.5 μm.
[0022] In the embodiments of this application, when the volume particle size distribution Dv50 of the graphite material meets the above range, the migration path of lithium ions inside the graphite particles can be shortened, thereby improving the rate performance of the battery cell.
[0023] In one possible implementation, the compaction density ρ of the graphite material satisfies: 1.7 g / cm³ 3 ≤ρ≤2.0g / cm 3 .
[0024] In the embodiments of this application, since the interlayer bonding force of graphite material weakens after oxidation intercalation, it is easier to be compressed, resulting in a higher compaction density of graphite material, which can improve the energy density of battery cells.
[0025] In a second aspect, a battery is provided, comprising a battery cell as described in the first aspect and any possible implementation thereof.
[0026] Thirdly, an electrical device is provided, including the battery of the second aspect. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of this application.
[0028] Figure 2 This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of this application.
[0029] Figure 3 This is a schematic diagram of a battery cell according to an embodiment of this application.
[0030] Figure 4 This is a schematic diagram of a battery according to an embodiment of this application.
[0031] Figure 5 This is a schematic diagram of an electrical device according to an embodiment of this application.
[0032] Explanation of reference numerals in the attached figures:
[0033] 1. Negative electrode sheet; 10. Negative current collector; 11. Negative electrode film layer; 111. First negative electrode active layer; 112. Second negative electrode active layer; 3. Battery cell; 31. Housing; 32. End cap assembly; 33. Electrode assembly; 34. Connecting component; 322. Electrode terminal; 330. Electrode assembly body; 331. Tab; 4. Battery; 5. Electrical device. Detailed Implementation
[0034] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the battery cell, its manufacturing method, the battery, and the power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0035] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0037] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0038] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0039] In recent years, rechargeable batteries have been widely used in many fields such as power tools, electronic products, electric vehicles, and aerospace due to their high energy density and long service life, thus achieving significant development.
[0040] The development of battery technology must consider multiple design factors simultaneously, such as energy density, cycle life, discharge capacity, charge / discharge rate, fast charging capability, reliability, and initial charge capacity. With the widespread use of batteries, the requirements for battery cycle performance and rate performance are gradually increasing. For lithium-ion battery anode materials, graphite is currently the primary choice due to its advantages of low voltage plateau and good conductivity. However, because the size of the lithium intercalation compounds formed during cycling is larger than the interlayer spacing of graphite, graphite undergoes volume expansion, thereby reducing the binding effect of the binder. This leads to stress release in the anode sheet, increased electrode thickness due to rebound, and increased risk of cell deformation and failure. Simultaneously, graphite has a relatively small specific surface area, resulting in insufficient channels for lithium ion entry and exit, which easily causes a rapid decrease in capacity during fast charging and discharging.
[0041] In view of this, this application provides a battery cell, comprising: a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer, the negative electrode film layer being disposed on at least one surface of the negative current collector, the negative electrode film layer comprising graphite material; the interlayer spacing of the graphite material is 0.3354 nm to 0.3370 nm; the actual specific surface area BET1 of the graphite material and the theoretical specific surface area BET2 of the graphite material satisfy: 10 ≤ BET1 / BET2 ≤ 30; where BET2 = 6 / (ρ × Dv50), ρ is the compacted density of the graphite material, in g / cm³. 3 Dv50 represents the volumetric particle size distribution of graphite materials, expressed in μm. Increasing the interlayer spacing of graphite materials can promote the migration of lithium ions between graphite layers and reduce the volume expansion caused by lithium delithiation and lithium intercalation, thereby improving the cycle performance of individual battery cells. Simultaneously, graphite materials have a large actual specific surface area and more active sites, which is beneficial for increasing the initial charge capacity of graphite and improving the rate performance of individual battery cells.
[0042] In addition, the following description, with appropriate reference to the accompanying drawings, will illustrate the battery cell, the method for preparing the battery cell, the battery, and the power-consuming device of this application.
[0043] [Battery cell]
[0044] Typically, a battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0045] In one embodiment of this application, a battery cell is provided, including a negative electrode sheet.
[0046] Figure 1This is a schematic diagram of the structure of a negative electrode sheet according to an embodiment of this application. For example, as shown... Figure 1 As shown, the negative electrode 1 includes a negative current collector 10 and a negative electrode film layer 11 disposed on at least one side surface of the negative current collector 10.
[0047] The negative electrode current collector 10 has two opposing surfaces along its thickness direction. The negative electrode film layer 11 can be disposed on one surface of the negative electrode current collector 10 or on both surfaces. As an example, such as... Figure 1 As shown, the negative electrode film layer 11 is disposed on both sides of the negative electrode current collector 10.
[0048] The negative electrode film layer 10 includes graphite material; wherein the interlayer spacing of the graphite material is 0.3354 nm to 0.3370 nm.
[0049] The graphite material can be micro-expanded graphite.
[0050] Interlayer spacing refers to the distance between layers. For example, graphite is a hexagonal network structure formed by sp2 hybrid orbitals and three adjacent carbon atoms forming three covalent single bonds. These network structures are connected by van der Waals forces to form parallel planes, thus constituting a lamellar structure. The distance between the layers is the interlayer spacing, which can be represented by d002, and satisfies the condition d002 = nλ / 2Sinθ (n = 1, 2, 3, etc.), where n represents the diffraction order, λ represents the wavelength of the X-rays used, and θ represents the angle between the diffracted beam and the incident ray. The interlayer space of graphite is both a lithium-ion storage space and a solid-phase diffusion channel for lithium ions. Increasing the interlayer spacing of graphite not only facilitates lithium-ion diffusion, reduces impedance, and improves kinetics, but also reduces the activation potential and electrode expansion of lithium-ion batteries during the first charge, and improves the rate charge and discharge performance to a certain extent.
[0051] After disassembling the battery cells, select electrode sheets with smooth surfaces and no active material loss. First, soak and clean them with DMC, then dry them to ensure the electrolyte is clean. Next, punch the electrode sheets into small round discs with a diameter of 14mm to separate the negative electrode film layer. Then grind them into regular powder, ensuring the sample amount is ≥2g. Add fine silicon powder at a ratio of C:Si = 5:1 and mix well as an internal standard (1g graphite 0.2g silicon). Then perform XRD testing to obtain the n, λ, and θ values of the negative electrode film layer. The interlayer spacing d002 can be calculated using the formula.
[0052] Understandably, in addition to obtaining graphite material from the negative electrode sheet by disassembling the battery cell, graphite material can also be obtained during the preparation of the negative electrode sheet.
[0053] The interlayer spacing of the graphite material can be 0.3354nm, 0.3355nm, 0.3356nm, 0.3357nm, 0.3358nm, 0.3359nm, 0.3360nm, 0.3361nm, 0.3364nm, 0.3366nm, 0.3368nm, 0.3370nm, or any value within the above range.
[0054] In some embodiments, the interlayer spacing of the graphite material is 0.3359 nm to 0.3361 nm.
[0055] The interlayer spacing of graphite materials can be 0.3359nm, 0.33591nm, 0.33593nm, 0.33598nm, 0.3360nm, 0.33603nm, 0.33605nm, 0.33608nm, 0.3361nm or any value within the above range.
[0056] The actual specific surface area BET1 and the theoretical specific surface area BET2 of graphite materials satisfy the following condition: 10 ≤ BET1 / BET2 ≤ 30; where BET2 = 6 / (ρ × Dv50), and ρ is the compacted density of the graphite material in g / cm³. 3 Dv50 represents the volumetric particle size distribution of graphite materials, in μm.
[0057] Take 5g of the graphite material powder prepared above and test it using a Tri-Star3020 surface area and pore size analyzer from Micromeritics, USA. The test standard is based on GB / T 19587-2017 to obtain the true specific surface area BET1 of the graphite material.
[0058] Dv50 can refer to the particle size at which the cumulative particle size distribution number of a sample reaches 50%, meaning that 50% of the particles are smaller than Dv50.
[0059] In this application, the compacted density of graphite material has a meaning known in the art and can be tested using instruments and methods known in the art. For example, it can be tested using an electronic pressure testing machine (e.g., UTM7305 type) according to standard GB / T24533-2009. An exemplary test method is as follows: Weigh 1g of graphite material and add it to a container with a base area of 1.327cm². 2 In the mold, pressure is applied to 2000 kg (equivalent to 20000 N), held for 30 s, then depressurized and held for 10 s. The compaction density of the graphite material under a force of 20000 N is then recorded and calculated.
[0060] In this application, BET1 / BET2 represents the degree of deviation between the actual specific surface area and the theoretical specific surface area of the graphite material, which can measure the degree of unevenness on the surface of the graphite material. By controlling the deviation between the theoretical and actual specific surface areas of the graphite material within a certain range, it is beneficial to improve the lithium-ion transport performance.
[0061] BET1 / BET2 can be 10, 11, 15, 17, 20, 22, 25, 27, 29, 30 or any value within the above range.
[0062] In some embodiments, 12 ≤ BET1 / BET2 ≤ 24.
[0063] BET1 / BET2 can be 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 or any value within the above range.
[0064] The increased interlayer spacing of graphite materials widens the diffusion channels for lithium ions, making it easier for lithium ions to intercalate and deintercalate at active sites within the graphite, and also provides space for expansion. Therefore, during the first charge and discharge cycle of the battery, it exhibits a lower activation potential and less significant volume expansion, improving the cycle performance and rate performance of the individual cells. The fact that the actual specific surface area of graphite materials is within the aforementioned range compared to the theoretical specific surface area results in a larger actual specific surface area. This leads to more active sites on the surface of the negative electrode film, improving the initial charge capacity and rate performance. Simultaneously, maintaining a specific surface area ratio of less than or equal to 30 helps reduce the contact area between the electrolyte and the graphite material, suppressing side reactions and improving the cycle life of the individual cells.
[0065] In some embodiments, the true specific surface area BET1 of the graphite material satisfies: 2m² 2 / g≤BET1≤6m 2 / g.
[0066] BET1 can be 2m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g or any value within the above range.
[0067] In some embodiments, 2.2m 2 / g≤BET1≤4.5m 2 / g.
[0068] BET1 can be 2.2m 2 / g, 2.5m 2 / g, 2.7m 2 / g, 3.0m 2 / g, 3.4m2 / g, 3.7m 2 / g, 4.0m 2 / g, 4.2m 2 / g, 4.5m 2 / g or any value within the above range.
[0069] The true specific surface area of graphite materials is greater than or equal to 2m². 2 At a concentration of / g, graphite materials have a large specific surface area, which can increase active sites, thus improving charging capacity and consequently enhancing the rate performance of individual battery cells; simultaneously, BET1 is less than or equal to 6m 2 At a rate of / g, the risk of side reactions can be reduced and the cycle performance of individual battery cells can be improved.
[0070] In some embodiments, the volumetric particle size distribution Dv50 of the graphite material satisfies: 16μm≤Dv50≤20μm.
[0071] The volumetric particle size distribution Dv50 of the graphite material can be 16μm, 16.5μm, 17μm, 17.5μm, 18μm, 18.5μm, 19μm, 19.5μm, 20μm or any value within the above range.
[0072] Optionally, 16.5μm≤Dv50≤17.5μm.
[0073] The volumetric particle size distribution Dv50 of the graphite material can be 16.5μm, 16.6μm, 16.7μm, 16.9μm, 17μm, 17.2μm, 17.4μm, 17.5μm or any value within the above range.
[0074] In the above scheme, by increasing the interlayer spacing and specific surface area of graphite material, but with little change in the Dv50 of graphite material, the migration path of lithium ions inside graphite particles can be shortened, thereby improving the rate performance of the battery cell.
[0075] In some embodiments, the compaction density ρ of the graphite material satisfies: 1.7 g / cm³ 3 ≤ρ≤2.0g / cm 3 .
[0076] The compacted density ρ of graphite materials can be 1.7 g / cm³. 3 1.8g / cm 3 1.9g / cm 3 2.0g / cm 3 Or any value within the above range.
[0077] In the above scheme, since the interlayer bonding force of graphite material weakens after oxidation intercalation, it is easier to be compressed. Therefore, a larger compaction density can be achieved when the cold pressing pressure of the negative electrode sheet is relatively small. As a result, the residual stress of the negative electrode sheet is reduced, the rebound of the electrode sheet is reduced, and the cycle performance of the battery cell is improved. At the same time, the increased compaction density can improve the energy density of the battery cell.
[0078] Figure 2 This is a schematic diagram of the negative electrode sheet according to an embodiment of this application. In some embodiments, such as Figure 2 As shown, the surface of the negative electrode current collector 10 is coated with a negative electrode film layer, wherein the negative electrode film layer includes a first negative electrode active layer 111 disposed on at least one surface of the negative electrode current collector 10; and a second negative electrode active layer 112 disposed on the surface of the first positive electrode active layer 111. The mass ratio A of graphite material in the first negative electrode active layer 111 and the mass ratio B of graphite material in the second negative electrode active layer 112 satisfy: A < B.
[0079] In the above scheme, the negative electrode film layer includes a first negative electrode active layer and a second negative electrode active layer. By controlling the mass ratio of graphite material in the first negative electrode active layer to be less than that in the second negative electrode active layer, more graphite material with a larger interlayer spacing and specific surface area is added to the coating on the surface of the negative electrode sheet, providing more transport channels for lithium ions, increasing active sites, improving charging capacity, and helping to reduce electrode structure damage caused by the volume expansion of active materials, thereby improving the cycle stability of the battery. Adding less graphite material to the lower layer can reduce the risk of volume expansion during cycling and improve the cycle performance of the battery cell.
[0080] In some embodiments, 1.02 ≤ B / A ≤ 1.10.
[0081] B / A can be 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10 or any value within the above range.
[0082] In the above scheme, when B / A is greater than or equal to 1.02, more graphite material is added to the second negative electrode active layer to improve the rate performance and charging capacity of the battery; and the mass ratio is controlled to be less than or equal to 1.10 to avoid side reactions caused by too much graphite material in the upper layer, while taking into account the cycle performance of the battery cells.
[0083] In some embodiments, the negative electrode film layer includes an adhesive; the mass ratio M of the adhesive in the first negative electrode active layer 111 and the mass ratio N of the adhesive in the second negative electrode active layer 112 satisfy: N < M.
[0084] In some embodiments, 0.5 ≤ N / M ≤ 0.8.
[0085] N / M can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or any value within the above range.
[0086] In the above scheme, the amount of binder added in the first negative electrode active layer is greater than the amount of binder added in the second negative electrode active layer. This can improve the adhesion of the negative electrode sheet, thereby improving the reliability of the battery cell. Furthermore, when the mass ratio of the binder meets the above range, it is beneficial to improve the adhesion while taking into account the rate performance of the battery cell.
[0087] [Positive electrode plate]
[0088] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.
[0089] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0090] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0091] In some embodiments, the positive electrode film layer may further include at least one of the positive electrode active materials known in the art for use in batteries: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0092] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid, polyimide, polyacrylonitrile, styrene-butadiene rubber, and fluorinated acrylate resins.
[0093] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0094] In some embodiments, the positive electrode film may optionally include a surfactant. As an example, the surfactant may include any one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and polyethylene glycol.
[0095] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0096] [Negative electrode plate]
[0097] As described above, the negative electrode current collector has two opposing surfaces along its thickness direction. The negative electrode film layer can be disposed on one surface of the negative electrode current collector or on both surfaces.
[0098] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0099] In some embodiments, the negative electrode film layer comprises graphite material; the interlayer spacing of the graphite material is 0.3354 nm to 0.3370 nm; the actual specific surface area BET1 of the graphite material and the theoretical specific surface area BET2 of the graphite material satisfy: 10 ≤ BET1 / BET2 ≤ 30; where BET2 = 6 / (ρ × Dv50), ρ is the compaction density of the graphite material, in g / cm³. 3 Dv50 represents the volumetric particle size distribution of graphite materials, in μm.
[0100] Graphite materials are prepared by a one-step oxidation intercalation method using concentrated sulfuric acid: graphite is mixed with concentrated sulfuric acid, and the mixture is mechanically stirred under water bath heating conditions to carry out oxidation intercalation. The water bath heating temperature range is 45℃~80℃, the mechanical stirring speed is 200rpm~800rpm, and the oxidation intercalation time is 0.5h~8h, optionally 1h~2h. After the reactants are cooled to room temperature, the graphite powder after the reaction is washed with deionized water, and then the product is dried at 60℃ for 12h to obtain graphite materials.
[0101] The concentration of concentrated sulfuric acid is 70% to 98%; the mass ratio of graphite to concentrated sulfuric acid is 1:2 to 1:10.
[0102] In some embodiments, the negative electrode active material included in the negative electrode film layer may include, in addition to graphite, other negative electrode active materials known in the art for use in batteries. As an example, the negative electrode active material may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0103] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0104] As described above, in some embodiments, the negative electrode film may optionally include conductive carbon. The conductive carbon may be selected from at least one of superconducting carbon, acetylene black, conductive carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0105] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0106] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive carbon, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0107] In some embodiments, the negative electrode sheet is subjected to a two-stage cold pressing method, where the first cold pressing is 80% to 90% of the target thickness, and the second cold pressing is to the target thickness, wherein the time interval between the first and second cold pressing is 1 hour to 48 hours.
[0108] In the above scheme, the secondary cold pressing method can release some of the internal stress of the electrode, reduce the risk of excessive electrode thickness rebound, and improve the reliability of the battery cell.
[0109] [Electrolytes]
[0110] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0111] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0112] For lithium-ion battery cells or lithium metal battery cells, the electrolyte salt may include one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0113] For lithium-ion battery cells or lithium metal battery cells, the solvent may include one or more of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0114] For sodium-ion battery cells or sodium metal battery cells, the electrolyte salt may include at least one of NaPF6, NaBF4, NaN(SO2F)2, NaClO4, NaAsF6, NaB(C2O4)2, NaBF2(C2O4), NaN(SO2RF)2, and NaN(SO2F)(SO2RF), where RF includes C b F 2b+1 b is an integer from 1 to 10; optionally, the electrolyte salt includes at least one of NaPF6, NaN(SO2F)2, and NaBF2(C2O4); optionally, b is an integer from 1 to 3; optionally, RF includes at least one of CF3, C2F5, and CF2CF2CF3.
[0115] For sodium-ion battery cells or sodium metal battery cells, the solvent may include at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone, 1,3-dioxolane, tetrahydrofuran, ethylene glycol dimethyl ether, and acetonitrile; optionally, the solvent may include at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and butyl carbonate.
[0116] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0117] [Isolation membrane]
[0118] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0119] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0120] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0121] [Battery Device]
[0122] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0123] In some implementations, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic or aluminum-plastic film; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0124] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 3 This is a square-structured battery cell 3, used as an example.
[0125] In some implementations, refer to Figure 3 The battery cell 3 includes a housing 31, an end cap assembly 32, and an electrode assembly 33 disposed within the housing 31. The housing 31 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 31 has an opening communicating with the receiving cavity, and the end cap assembly 32 can be closed by covering the opening. The end cap assembly 32 includes electrode terminals 322, such as... Figure 3 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal. The electrode assembly 33 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 33. The positive electrode sheet, negative electrode sheet, and separator can be formed into the electrode assembly 33 via a winding process or a stacking process. The electrode assembly 33 includes an electrode assembly body 330 and tabs 331 extending from the electrode assembly body 330. The battery cell 3 also includes a connecting member 34 for connecting the tabs 331 and the electrode terminals 322 of the electrode assembly 33. The battery cell 3 can contain one or more electrode assemblies 33, which can be selected by those skilled in the art according to specific practical needs.
[0126] In some implementations, the secondary batteries can be assembled into a battery module, and the number of secondary batteries contained in the battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.
[0127] Figure 4 This is a battery 4 as an example. Referring to the figure, in battery 4, multiple battery cells 3 can be arranged sequentially along the length of battery 4. Of course, they can also be arranged in any other arbitrary way. Furthermore, these multiple battery cells 3 can be fixed in place by fasteners.
[0128] Optionally, the battery 4 may also include a housing with a receiving space in which multiple battery cells 3 are housed.
[0129] In some embodiments, the battery modules described above can also be assembled into a battery / battery pack. The number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0130] [Electrical appliances]
[0131] In addition, this application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0132] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0133] Figure 5 Here is an example of an electrical device 5. This electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this electrical device, a battery pack or battery module can be used.
[0134] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.
[0135] [Example]
[0136] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0137] Example 1
[0138] (1) Preparation of positive electrode sheet
[0139] Lithium iron phosphate (LiFePO4), polyvinylidene fluoride (PVDF), and surfactant were mixed uniformly at a mass ratio of 97.5:2:0.5 and dissolved in N-methylpyrrolidone (NMP). The mixture was thoroughly stirred to prepare a positive electrode slurry. This slurry was then uniformly coated onto two opposite surfaces of a 15 μm thick aluminum foil current collector. After drying, cold pressing, and slitting, the positive electrode sheet was obtained. The coating weight of the positive electrode sheet was 0.6160 g / 1540.25 mm. 2 The cold-pressed thickness of the positive electrode sheet is 0.1719 mm, and the compaction density is 2.55 g / cm³. 3 .
[0140] (2) Preparation of negative electrode sheet
[0141] Artificial graphite was mixed with 90% concentrated sulfuric acid (an oxidation intercalating agent) at a mass ratio of 1:4. The mixture was then subjected to oxidation intercalation under water bath heating conditions with mechanical stirring for 1.5 hours. The water bath heating temperature was 60°C and the mechanical stirring speed was 500 rpm. After the reactants were cooled to room temperature, the powder was washed with deionized water to remove residual acid. The product was then dried at 60°C for 12 hours to obtain graphite material.
[0142] A negative electrode active material (graphite), a conductive agent (conductive carbon black), a binder (styrene-butadiene rubber), and a thickener (sodium carboxymethyl cellulose, CMC-Na) were dissolved in deionized water at a mass ratio of 96:0.7:2.6:0.7 and thoroughly mixed to prepare a negative electrode film slurry. This slurry was then coated onto two opposite surfaces of a 6 μm thick copper foil current collector. After drying, cold pressing, and slitting, the negative electrode sheet was obtained. The cold pressing was performed in two stages: a first cold pressing to 90% of the target thickness, followed by a 24-hour interval, and a second cold pressing to the target thickness. The cold-pressed thickness of the negative electrode sheet was 0.1182 mm, and the compaction density was 1.65 g / cm³. 3 .
[0143] (3) Separating membrane
[0144] A polyethylene film with a thickness of 12μm was used as the separator.
[0145] (4) Preparation of electrolyte
[0146] The organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain a mixed solvent. Then, fully dried lithium salt (LiPF6) was dissolved in the above mixed solvent at a ratio of 1 mol / L to obtain an electrolyte. The electrolyte was injected into the battery cell in two stages, with the first injection ratio being 85% and the second injection ratio being 15%.
[0147] (5) Preparation of battery cells
[0148] After the positive electrode, separator, and negative electrode are wound to form a cell with a capacity of approximately 2.5Ah, they are placed in an aluminum-plastic film and then subjected to processes such as liquid injection, sealing, formation, and aging to obtain a soft-pack lithium-ion battery.
[0149] Example 2
[0150] Compared to Example 1, Example 2 uses the same negative electrode active material, but the negative electrode sheet is double-coated. The negative electrode active material (graphite), conductive carbon black (conductive agent), styrene-butadiene rubber (styrene-butadiene rubber) (binder), and sodium carboxymethyl cellulose (CMC-Na) (thickener) are dissolved in deionized water at a mass ratio of 96.4:0.6:2.3:0.7 and thoroughly mixed to prepare the first negative electrode active layer slurry. The same materials are then dissolved in deionized water at a mass ratio of 97.5:0.7:1.2:0.6 and thoroughly mixed to prepare the second negative electrode active layer slurry. The first negative electrode active layer slurry is coated on two opposite surfaces of a 6 μm thick copper foil negative electrode current collector, and the second negative electrode active layer slurry is coated on two opposite surfaces of the first negative electrode active layer. After drying, cold pressing, and slitting, the negative electrode sheet is obtained.
[0151] Example 3
[0152] Compared with Example 2, in Example 3, the artificial graphite and concentrated sulfuric acid were mechanically stirred and oxidized for 1 hour at 60°C.
[0153] Example 4
[0154] Compared with Example 2, in Example 4, the artificial graphite and concentrated sulfuric acid were mechanically stirred and oxidized for 2 hours at 60°C.
[0155] Comparative Example 1
[0156] Compared with Example 1, the negative electrode active material in Comparative Example 1 is artificial graphite. The negative electrode active material artificial graphite, conductive agent conductive carbon black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in deionized water at a mass ratio of 96:0.7:2.6:0.7 and thoroughly stirred and mixed to prepare a negative electrode film slurry. The negative electrode film slurry is coated on two opposite surfaces of a negative electrode current collector copper foil with a thickness of 6 μm. After drying, cold pressing, and slitting, the negative electrode sheet is obtained.
[0157] The battery cells obtained in Examples 1-4 and Comparative Example 1 were subjected to parameter and performance tests. The test results are shown in Table 1 below.
[0158] Table 1: Specific parameters of Examples 1-4 and Comparative Example 1
[0159]
[0160] [True Specific Surface Area Testing Method]
[0161] After measuring the amount of gas adsorbed on the solid surface at a pressure of 20 MPa under constant temperature, the amount of monolayer adsorption of the sample was obtained based on the Brown-Etter-Taylor (BET) multilayer adsorption theory and its formula, thereby calculating the specific surface area of the graphite material.
[0162] [Test of volumetric particle size distribution]
[0163] The volumetric particle size distribution can be determined using a particle size analyzer-laser diffraction method. Specifically, refer to standard GB / T19077-2016, using a laser diffraction scattering particle size analyzer, and perform measurements according to the manufacturer's instructions. For example, take an appropriate amount of sample (graphite material), which can be obtained as powder through forward acquisition (e.g., homemade or purchased), or as powder obtained from disassembling battery products. Use a Malvern 2000 (MasterSizer 2000) laser particle size analyzer to test the average volumetric particle size of the sample material. Take an appropriate amount of the sample to be tested (the sample concentration should be 8-12% opacity), add 20 ml of deionized water, and simultaneously incubate for 5 minutes (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, measure the sample according to GB / T19077-2016 / ISO 13320:2009 standard.
[0164] [Test of compaction density]
[0165] According to standard GB / T24533-2009, the test was conducted using an electronic pressure testing machine (e.g., UTM7305). 1g of graphite material was weighed and added to a substrate with a base area of 1.327 cm². 2 In the mold, pressure is applied to 2000 kg (equivalent to 20000 N), held for 30 s, then depressurized and held for 10 s. The compaction density of the graphite material under a force of 20000 N is then recorded and calculated.
[0166] [Method for measuring interlayer spacing]
[0167] After disassembling the battery cells, select electrode sheets with smooth surfaces and no active material loss. First, soak and clean them with DMC, then dry them to ensure the electrolyte is thoroughly cleaned. Next, punch the electrode sheets into small round sheets with a diameter of 14mm to separate the negative electrode film layer. Then, grind the negative electrode film layer into a standard powder. Weigh out a sample of graphite material powder with a weight ≥2g and a particle size <10μm (if the particle size is too large, it needs to be ground). Add fine silicon powder at a ratio of C:Si = 5:1 and mix well as an internal standard (1g graphite = 0.2g silicon). Then perform XRD testing to obtain the n, λ, and θ values of the negative electrode film layer. The interlayer spacing d002 can be calculated using the formula: d002 = nλ / 2Sinθ (n = 1, 2, 3, etc.), where n represents the diffraction order, λ represents the wavelength of the X-rays used, and θ represents the angle between the diffracted beam and the incident ray. In addition to obtaining graphite material from the negative electrode sheet by disassembling the battery cells, graphite material can also be obtained during the preparation of the negative electrode sheet.
[0168] [DCR Testing Method]
[0169] First, a capacity test is performed to determine the cell capacity C. The battery cell is fully charged at a constant current and constant voltage of 0.33C; then discharged to 0.5C Ah to adjust to 50% SOC, and then discharged at a constant rate of 4C for 30 seconds, and then charged at a constant rate of 4C for 30 seconds. The voltage change U0 is recorded to calculate the DC internal resistance (DCR) of the battery cell = U0 / I, where I = the current corresponding to the 4C rate.
[0170] [Charge / Discharge Capacity Test Method]
[0171] After the prepared coin cells were left to stand for 5 hours, they were discharged at a constant current of 0.1C to 0.005V, left to stand for 5 minutes, and then discharged at a constant current of 50μA to 0.005V. After leaving to stand for 5 minutes, they were discharged at a constant current of 10μA to 0.005V. Then, they were charged at a constant current of 0.1C to 2V, and the charge and discharge capacities were recorded. The charge and discharge capacities were calculated as a percentage of the graphite material's mass to obtain the specific charge and discharge capacities of the graphite material.
[0172] [Rebound rate of negative electrode sheet]
[0173] The design thickness of the negative electrode sheet after cold pressing is denoted as h1, and the electrode sheet thickness after battery formation is denoted as h2. (h2-h1) / h1 is denoted as the rebound rate of the negative electrode sheet after formation. The electrode sheet thickness after the battery is fully charged (100% SOC state of charge) is denoted as h3, and (h3-h1) / h1 is denoted as the rebound rate of the negative electrode sheet after full charge.
[0174] Table 2: Test results of Examples 1-4 and Comparative Example 1
[0175]
[0176] Combined with Examples 1-4 and Comparative Example 1, compared with Comparative Example 1 without the addition of graphite material, Examples 1-4 can reduce the rebound rate of the electrode after formation and after full charging, and reduce the internal resistance.
[0177] As shown in Examples 1 and 2, when the negative electrode film layer is designed as a double layer, adding more graphite material to the upper layer and more binder to the lower layer can reduce the electrode rebound rate and reduce internal resistance, which is beneficial to improving the cycle performance of the battery cell.
[0178] As shown in Examples 2-4, by controlling the oxidation intercalation time, the interlayer spacing and BET1 / BET2 ratio of the graphite material are kept within a certain range. With increasing oxidation intercalation time, the interlayer spacing of the graphite material increases, leading to improved charge / discharge specific capacity and reduced electrode rebound rate; however, the internal resistance also increases. Therefore, controlling the interlayer spacing and specific surface area ratio of the graphite material within the aforementioned range is beneficial for improving the cycle performance and rate performance of the battery cells.
[0179] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A battery cell, characterized in that, include: A negative electrode sheet, the negative electrode sheet comprising a negative current collector and a negative electrode film layer, the negative electrode film layer being disposed on at least one surface of the negative current collector, the negative electrode film layer comprising a graphite material; The interlayer spacing of the graphite material is 0.3354 nm to 0.3370 nm; The actual specific surface area BET1 of the graphite material and the theoretical specific surface area BET2 of the graphite material satisfy the following condition: 10≤BET1 / BET2≤30; Where BET2=6 / (ρ×Dv50), ρ is the compacted density of the graphite material, in g / cm³. 3 Dv50 is the volumetric particle size distribution of the graphite material, in μm.
2. The battery cell according to claim 1, characterized in that, 12≤BET1 / BET2≤24.
3. The battery cell according to claim 1 or 2, characterized in that, The interlayer spacing of the graphite material is 0.3359 nm to 0.3361 nm.
4. The battery cell according to any one of claims 1 to 3, characterized in that, The true specific surface area BET1 of the graphite material satisfies: 2m² 2 / g≤BET1≤6m 2 / g.
5. The battery cell according to claim 4, characterized in that, 2.2m 2 / g≤BET1≤4.5m 2 / g。 6. The battery cell according to any one of claims 1 to 5, characterized in that, The negative electrode film layer includes a first negative electrode active layer and a second negative electrode active layer, wherein the first negative electrode active layer is disposed between the negative electrode current collector and the second negative electrode active layer; The mass ratio A of the graphite material in the first negative electrode active layer and the mass ratio B of the graphite material in the second negative electrode active layer satisfy the condition: A < B.
7. The battery cell according to claim 6, characterized in that, 1.02≤B / A≤1.
10.
8. The battery cell according to claim 6 or 7, characterized in that, The negative electrode film layer includes a binder; The mass percentage M of the binder in the first negative electrode active layer and the mass percentage N of the binder in the second negative electrode active layer satisfy the condition: N < M.
9. The battery cell according to claim 8, characterized in that, 0.5≤N / M≤0.
8.
10. The battery cell according to any one of claims 1 to 9, characterized in that, The volumetric particle size distribution Dv50 of the graphite material satisfies: 16μm≤Dv50≤20μm.
11. The battery cell according to claim 10, characterized in that, 16.5μm≤Dv50≤17.5μm.
12. The battery cell according to any one of claims 1 to 11, characterized in that, The compacted density ρ of the graphite material satisfies: 1.7 g / cm³ 3 ≤ρ≤2.0g / cm 3 .
13. A battery, characterized in that, Includes the battery cell as described in any one of claims 1-12.
14. An electrical appliance, characterized in that, Includes the battery as described in claim 13.